Peningkatan Pendapatan dan Ketahanan Pangan Keluarga melalui Teknik Pengolahan Teh di Dusun Kembangan, Desa Mojojajar, Kecamatan Kemlagi, Kabupaten Mojokerto - Fajar Budiyanto; Mohammad Nashir A; Hery Setiawan; Defi Sri L; Devi Putri A; Galuh Prameswari; Dinda Tri R.; Silahul Maulana Syah.; Era Septya W.; Erisma Dwi R.; Mochammad Muzakki H.S.; Moh. Rifaldo Dimas S.; Muhammad Wisnu I.H.; Nanda Rizal P.; Riris Wahyuningtyas; Isfatul Fadila C.S.; Dea Sabilillah; Syarif Sulthon H.; Silvia Gita F.A.; Silvi Rani P.; Meliza Fatmawati; Herfanda Yoga P.P. (Politeknik Kampar, 2023)
This activity aims to empower the Kembangan hamlet community to increase family income and food security through utilizing the potential of tea in the area. Activities were carried out involving lecturers and students from local educational institutions, with the active participation of 8 hamlet residents. The method used involves the process of collecting field data, analyzing the potential of tea in the local area, as well as providing training in tea processing techniques. Lecturers as facilitators provide knowledge and skills to students and residents in managing tea plants efficiently and using appropriate processing techniques. The results of this activity include improving the quality of tea, diversifying tea processed products, and implementing sustainable agricultural practices. Apart from that, residents are also guided in marketing local tea products, both conventionally and via digital platforms, in order to increase market access and income.